RATIO LIQUIDITY, SOLVENCY AND PROFITABILITY ANALYSIS (CASE STUDY OF PT SUCOFINDO PERSERO MEDAN) - Anan , Malesa (Jurnal Riset Akuntansi & Keuangan, 2023)
This research is a descriptive approach carried out at PT. Sucofindo (Persero) Medan, Jalan Anggada I No. 1, Belawan I, Medan. The type of data in this study is secondary data sourced from PT Sucofindo’s official website, namely www.sucofindo.co.id, in the form of financial report data for PT Sucofindo Indonesia Medan from December 2020 to December 2021, which contains a balance sheet and income statement. Techniques for collecting data, including documentation and a review of the literature The data analysis technique uses horizontal analysis techniques and descriptive analysis by comparing the financial statements for some time until development information is found. The purpose of this study was to determine the level of liquidity, solvency, and profitability of PT. Sucofondo (Persero) Medan in the period 2020 to 2021. From the analysis of the financial statements, it was found that the current ratio has increased from 2020 to 2021 by 0.23 times, the quick ratio has increased by 0.25 times, and the cash ratio has increased by 0.57 times. Likewise, the debt ratio also increased by 0.01%, and the debt-to-equity ratio rose by 0.02%. Then the return on assets also rose 0.01%, the return on equity rose 0.02%, the operating profit margin decreased by 0.22%, and the NPM rose 0.17%.